2019
DOI: 10.1371/journal.pone.0210610
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient variability in human milk from donors to a milk bank: Implications for feeding preterm infants

Abstract: Background and objectiveThe composition of human milk varies widely and impacts the ability to meet nutrient requirements for preterm infants. The purpose of this study is to use a large dataset of milk composition from donors to a milk bank to: (1) describe the macronutrient variability in human milk and how it contributes to the ability to meet the protein and calorie targets for the preterm infant using fortification with commercially available multi-nutrient fortifiers; (2) assess how temporal versus subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 40 publications
7
53
0
2
Order By: Relevance
“…As a baseline validation, protein concentration was lower in DBM than in preterm milk, which validates the results of a previous study [23]. DBM is often donated from term-delivering mothers at late lactation time, whereas the MBM examined in this study was from preterm mothers at early lactation time, which may have higher antibody concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…As a baseline validation, protein concentration was lower in DBM than in preterm milk, which validates the results of a previous study [23]. DBM is often donated from term-delivering mothers at late lactation time, whereas the MBM examined in this study was from preterm mothers at early lactation time, which may have higher antibody concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…Although derived from different statistical methods, the coefficients of determination for between-subject effects and lactation time effects are comparable with that described in the study by John et al (47) which analysed the macronutrient data of 1119 human milk samples from 443 individual donors to a milk bank (subject effects 67-79 % of the variance v. 51-82 % in the study by John et al). Despite the amount of inter-individual variability in HDM, it is perhaps reproducible between cohorts.…”
Section: Discussionsupporting
confidence: 65%
“…NIR analysis revealed that the target-pooled DBM samples contained similar calories (18.7 vs. 18.0–18.7 kcal/oz) and protein concentrations (0.91 vs. 0.88–1.0 g/dL) compared to other recent analyses of multi-donor random-pooled DBM [18,19]. However, in these studies, samples were measured pre-pasteurization.…”
Section: Discussionmentioning
confidence: 77%